(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the problems of translating the text of works of art from one language into another language and the classification of their features, and also analyzes the features of the problems of translating works of art using examples.